2007
DOI: 10.1007/s10620-007-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Sonography in Predicting Steatosis and Fibrosis in Chronic Hepatitis C

Abstract: The accuracy and clinical significance of sonography (US) in demonstrating fatty liver and hepatic fibrosis in chronic hepatitis C (CHC) are rarely reported. US had sensitivity 71.1%, specificity 72.9%, 58.7% positive predictive value (PPV), and 82.3% negative predictive value (NPV) in demonstrating histological steatosis > or =5%. US had sensitivity 85.7%, specificity 60.4%, 13% PPV, and 98.4% NPV in demonstrating histological steatosis > or =30% with clinical significance in predicting prognosis and therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…66 Although several specific features have been identified to be unique to NAFLD when using ultrasound, and the inter-observer agreement for identifying these features has been shown to be relatively good, the sensitivity of these findings is considerably lower when the overall content of hepatic steatosis is < 20%. 6775 Furthermore, patient demographics (obesity) and co-existing conditions (hepatitis C) have been shown to further reduce the sensitivity of this diagnostic tool, 7579 which significantly impacts its ability to reliability distinguish between the presence or absence of hepatic steatosis among at-risk individuals.…”
Section: Mri-based Assessment Of Hepatic Steatosismentioning
confidence: 99%
“…66 Although several specific features have been identified to be unique to NAFLD when using ultrasound, and the inter-observer agreement for identifying these features has been shown to be relatively good, the sensitivity of these findings is considerably lower when the overall content of hepatic steatosis is < 20%. 6775 Furthermore, patient demographics (obesity) and co-existing conditions (hepatitis C) have been shown to further reduce the sensitivity of this diagnostic tool, 7579 which significantly impacts its ability to reliability distinguish between the presence or absence of hepatic steatosis among at-risk individuals.…”
Section: Mri-based Assessment Of Hepatic Steatosismentioning
confidence: 99%
“…Nevertheless, the ability of ultrasound to evaluate the presence and degree of LS remains debatable. In fact, although some authors have shown that the bright liver echo pattern (BLP) is strongly correlated with the diagnosis of hepatic steatosis [6][7][8][9][10][11][12][13], other authors think that this pattern is non-specific because the liver echogenicity on ultrasonography also increases with liver fibrosis [14][15][16][17][18][19][20]. Recently, the simultaneous presence of BLP, posterior attenuation, and/or areas with different patterns of fat infiltration (so-called skip areas) around gallbladder or near the portal vein [21] have been identified as distinctive signs of steatosis involving a number of hepatocytes in a microscopic field [30 % [11].…”
Section: Introductionmentioning
confidence: 99%
“…These drawbacks limit the use of ultrasound in longitudinal studies. To date, grayscale B-mode ultrasound is not considered a replacement for liver biopsy in evaluating fatty liver [18].…”
Section: Introductionmentioning
confidence: 99%